KISSPEPTIN LEVELS IN WOMEN WITH PCOS: A MARKER FOR HORMONAL DYSREGULATION - Dr Purnima Kiran Gautam; Dr Pikee Saxena; Dr Nikita Garkhel; Dr Anjani Sai Kuracha (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Polycystic Ovary Syndrome (PCOS) is a prevalent endocrine disorder among women of reproductive age, characterized by hyperandrogenism, oligo/anovulation, and polycystic ovarian morphology. Emerging research has highlighted kisspeptin, a neuropeptide encoded by the KISS1 gene and acting via the G-protein-coupled receptor GPR54 (KISS1R), as a potential biomarker of hormonal dysregulation in PCOS. The objective of the study is to evaluate serum kisspeptin levels in women with PCOS and their correlation with gonadotropins and other reproductive hormones, assessing its role as a marker of neuroendocrine dysfunction.Materials and Methods: This comparative study included 180 women (90 PCOS cases and 90 age-matched controls), aged 18–40 years, at a tertiary care center. PCOS diagnosis was based on the Rotterdam criteria. Serum kisspeptin and reproductive hormones, including LH, FSH, testosterone, progesterone, prolactin, SHBG, and DHEAS, were quantified using ELISA and immunoassays. Data were analyzed using SPSS v26.0.Results: Kisspeptin levels were significantly elevated in PCOS patients (289.0 ± 93.3 pg/mL) compared to controls (240.8 ± 110.6 pg/mL, p = 0.002). Positive correlations were observed between kisspeptin and LH (r = 0.564), FSH (r = 0.626), testosterone (r = 0.447), and SHBG (r = 0.497), while prolactin (r = -0.539) and progesterone (r = -0.553) showed negative correlations (p < 0.05 for all). No significant correlation with BMI or thyroid parameters was observed.Conclusion: Elevated kisspeptin levels and their strong association with key reproductive hormones suggest its integral role in the hypothalamic–pituitary–gonadal (HPG) axis dysregulation characteristic of PCOS. Kisspeptin holds promise as a biomarker for identifying hormonal imbalance, independent of age and metabolic status.